Synthesis method of boron-oxygen co-doped graphite phase carbon nitride nanosheet and application thereof in killing drug-resistant bacteria

CN117983273BActive Publication Date: 2026-10-23GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410121764.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2026-10-23
Estimated Expiration
2044-01-30

AI Technical Summary

Technical Problem

该硼氧双掺杂石墨相氮化碳纳米片具有对可见光的强烈吸收和优异的光生电子-空穴分离效率,克服单一的氮化碳光催化剂在光催化杀菌性能方面的不足,可将其用于饮用水或医疗废水中病原菌的消毒

Benefits of technology

[0025]本发明通过酸处理富氮前驱体实现石墨相氮化碳纳米片的片层结构中氧元素的引入,同时利用含硼化合物在反应过程中剪切氮化碳骨架实现硼元素的掺杂。硼原子的掺杂将石墨相氮化碳的禁带宽度变窄,形成中间杂质能级,提高了光生载流子分离率;氧原子的引入进一步减小禁带宽度,提升对太阳光的响应能力,实现全光谱的利用。本发明有效解决了现有石墨相氮化碳光生载流子复合严重、光响应范围有限的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117983273B_ABST
    Figure CN117983273B_ABST
Patent Text Reader

Abstract

The application discloses a synthesis method of boron-oxygen double-doped graphite phase carbon nitride nanosheets and application of the boron-oxygen double-doped graphite phase carbon nitride nanosheets in killing drug-resistant bacteria. The synthesis method of the boron-oxygen double-doped graphite phase carbon nitride nanosheets comprises the following steps: mixing and stirring acid and a precursor, drying white powder obtained after ice bath crystallization; placing the white powder in a muffle furnace to obtain oxygen-doped carbon nitride through high-temperature polymerization; and performing high-temperature polymerization on the oxygen-doped carbon nitride and a boron-containing compound in a tube furnace, and obtaining the boron-oxygen double-doped graphite phase carbon nitride nanosheets through washing and drying after reaction. The boron-oxygen double-doped graphite phase carbon nitride nanosheets prepared by the application have a tunable energy band structure, expand the response range of original graphite phase carbon nitride to visible light, and have a more efficient photo-generated carrier separation and transmission capacity. Meanwhile, the rich nitrogen defect structure provides more unsaturated active sites for the inactivation process of pathogenic bacteria and is beneficial to enhancing the attachment probability of pathogenic bacteria and the photocatalytic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic sterilization technology, specifically to a method for synthesizing boron-oxygen dual-doped graphitic carbon nitride nanosheets and their application in killing drug-resistant bacteria. Background Technology

[0002] Drug-resistant bacteria in water pose a significant threat to human drinking water health. Their presence can induce a range of inflammations, leading to various human diseases. Therefore, safely and efficiently inactivating pathogens is crucial. Currently, ultraviolet (UV) and ozone disinfection are the main methods, but they suffer from high costs and the unavoidable generation of toxic byproducts. Solar disinfection, utilizing clean energy, has attracted widespread attention in the disinfection field in recent years. Photocatalytic sterilization is a green, mild, and economical disinfection strategy. Photocatalytic sterilization materials directly utilize sunlight to convert light energy into chemical energy, generating a series of reactive oxygen species during the photocatalytic process to inactivate pathogens. Graphite-phase carbon nitride (g-C3N4) possesses advantages such as simple preparation, abundant raw materials, good thermal and chemical stability, excellent visible light response, suitable conduction and valence band positions, and tunable band structure, making it one of the most promising antibacterial materials currently available.

[0003] However, pristine graphitic carbon nitride only responds to visible light below 450 nm, has a small specific surface area, suffers from severe photogenerated electron-hole recombination, and exhibits poor photocatalytic bactericidal performance. Common modification methods include constructing heterojunctions, morphology manipulation, elemental doping, and molecular doping. For example, the introduction of oxygen facilitates the transfer of photoexcited electrons to the region surrounding oxygen atoms, achieving efficient utilization of photogenerated carriers; the introduction of boron can adjust the conduction band position of g-C3N4, optimizing its band structure, enabling effective absorption of visible light and significantly increasing its own oxidation driving force. The introduction of nitrogen defect sites can form an electron-rich structure in the graphitic carbon nitride structure, making the charge density distribution more localized and enhancing light absorption and carrier separation capabilities.

[0004] However, to date, there are still no related studies or reports on the preparation methods of graphitic carbon nitride nanosheets that simultaneously achieve the above two modifications and their application in killing drug-resistant bacteria. Summary of the Invention

[0005] To address the problems existing in the prior art, this invention provides a method for synthesizing boron-oxygen dual-doped graphitic carbon nitride nanosheets. These boron-oxygen dual-doped graphitic carbon nitride nanosheets exhibit strong absorption of visible light and excellent photogenerated electron-hole separation efficiency, overcoming the shortcomings of single carbon nitride photocatalysts in photocatalytic sterilization performance. They can be used for disinfection of pathogens in drinking water or medical wastewater.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] The first aspect of this invention provides a method for synthesizing boron-oxygen co-doped graphitic carbon nitride nanosheets, comprising the following steps:

[0008] (1) The acid and the precursor were mixed and stirred, crystallized in an ice bath, and then dried to obtain a white powder; the white powder was placed in a muffle furnace and polymerized at high temperature to obtain oxygen-doped carbon nitride.

[0009] (2) The oxygen-doped carbon nitride and boron-containing compounds are polymerized at high temperature in a tube furnace, and the reaction is followed by washing and drying to obtain the boron-oxygen dual-doped graphite phase carbon nitride nanosheets.

[0010] Preferably, the acid is one of concentrated nitric acid, concentrated sulfuric acid, acetic acid, and phosphoric acid.

[0011] Preferably, the precursor is at least one of urea, melamine, dicyandiamide, and thiourea.

[0012] Preferably, in step (1), the acid and precursor are mixed and stirred for 120-240 min, and the mixing and stirring temperature is 30-50℃.

[0013] Preferably, in step (1), the high-temperature polymerization is high-temperature calcination, the high-temperature polymerization temperature is 450℃-650℃, the time is 3-5h, and the heating rate is 2℃ / min-15℃ / min.

[0014] Preferably, in step (2), the boron-containing compound is at least one of boric acid and sodium borohydride.

[0015] Preferably, in step (2), the mass ratio of the oxygen-doped carbon nitride to the boron-containing compound is (3-5):1.

[0016] Preferably, in step (2), the high-temperature polymerization is high-temperature calcination, the high-temperature polymerization temperature is 300℃-600℃, the time is 30min-180min, and the heating rate is 2℃ / min-15℃ / min.

[0017] Preferably, in step (2), during the high-temperature polymerization process in the tubular furnace, argon, nitrogen, or a vacuum state is introduced into the furnace.

[0018] The second aspect of the present invention provides a boron-oxygen dual-doped graphitic carbon nitride nanosheet, which is prepared by the synthesis method of the boron-oxygen dual-doped graphitic carbon nitride nanosheet.

[0019] The third aspect of this invention provides an application of boron-oxygen dual-doped graphitic carbon nitride nanosheets in killing drug-resistant bacteria. The steps for killing drug-resistant bacteria are as follows: mixing the original bacterial solution with physiological saline and adding a photocatalyst to obtain a suspension; turning on the light source to carry out a photocatalytic sterilization reaction;

[0020] The drug-resistant bacteria are one or more of the following: gentamicin-resistant Escherichia coli (GEN), polymyxin-resistant Escherichia coli (MCR), ceftazidime-resistant Escherichia coli (CTX), and Staphylococcus aureus; the photocatalyst is the boron-oxygen dual-doped graphitic carbon nitride nanosheets.

[0021] Preferably, the bacterial concentration in the suspension is 6.0-8.0 log₂O₅. 10 The concentration of photocatalyst in the suspension is 100-2000 mg / L (CFU / mL); the light source is a xenon lamp, an LED light source, or a natural solar light source.

[0022] Preferably, the drug-resistant bacterium is gentamicin-resistant Escherichia coli (GEN).

[0023] More preferably, the concentration of the photocatalyst in the suspension is 500 mg / L.

[0024] Compared with the prior art, the beneficial effects of the present invention are:

[0025] This invention introduces oxygen into the layered structure of graphitic carbon nitride nanosheets by acid treatment of a nitrogen-rich precursor, while simultaneously doping with boron by utilizing boron-containing compounds to shear the carbon nitride framework during the reaction. Boron doping narrows the band gap of graphitic carbon nitride, forming intermediate impurity energy levels and improving the photogenerated carrier separation rate. The introduction of oxygen atoms further reduces the band gap, enhancing the response to sunlight and enabling full-spectrum utilization. This invention effectively solves the problems of severe photogenerated carrier recombination and limited photoresponse range in existing graphitic carbon nitride systems.

[0026] The boron-oxygen dual-doped graphitic carbon nitride nanosheets prepared by this invention possess a tunable band structure, extending the response range of the original graphitic carbon nitride to visible light and exhibiting more efficient photogenerated carrier separation and transport capabilities. Simultaneously, the abundant nitrogen-deficient structures provide more unsaturated active sites for the pathogen inactivation process and enhance the adhesion probability between pathogens and photocatalytic materials.

[0027] The boron-oxygen dual-doped graphitic carbon nitride nanosheets prepared by the present invention are a photocatalytic material with highly efficient bactericidal properties. They can directly utilize sunlight to inactivate drug-resistant bacteria in flowing water, making them an environmentally friendly sterilization material. Attached Figure Description

[0028] Figure 1 TEM image of boron-oxygen dual-doped carbon nitride (HBCN) photocatalytic bactericidal material;

[0029] Figure 2 The results of testing the bactericidal performance of different photocatalytic materials CN, HCN, BCN, and HBCN against gentamicin-induced Escherichia coli (GEN);

[0030] Figure 3 Tests were conducted on the bactericidal performance of HBCN, a boron-oxygen dual-doped carbon nitride material, against various pathogens.

[0031] Figure 4 The study investigated the inactivation effect of HBCN, a boron-oxygen dual-doped carbon nitride material with different concentrations, against gentamicin-induced Escherichia coli (E. coli). Detailed Implementation

[0032] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0033] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.

[0034] Example 1

[0035] Dicyandiamide (DCDA) treated with concentrated HNO3 was used as a precursor, and the specific treatment process is as follows:

[0036] 2.0 g of dicyandiamide was added to 40.0 mL of an aqueous solution containing 5 mL of concentrated nitric acid (HNO3). The resulting precursor was stirred at 40 °C for 180 min, and the product was crystallized in an ice bath at 0 °C. The crystals were then dried overnight in an oven at 60 °C. After drying, the product was heated in a muffle furnace at 550 °C for 4.0 °C min. -1 The mixture was calcined at a high heating rate and held for 4 hours. The resulting pale yellow solid was then ground to obtain a pale yellow powder, HCN (oxygen-doped carbon nitride).

[0037] HCN and NaBH4, in a mass ratio of 4:1, were finely ground in a mortar and then uniformly dispersed in a porcelain boat. The porcelain boat was then placed in a tube furnace under an argon atmosphere. The furnace program was set to heat to 400°C at a rate of 10°C / min and hold for 1 hour. After calcination, the resulting brownish-red product was washed several times with ethanol and deionized water. The washed material was then vacuum-dried at 80°C for 10 hours. The final collected brownish-red powder is HBCN (boron-oxygen dual-doped carbon nitride), a boron-oxygen dual-doped and nitrogen-deficient graphitic carbon nitride photocatalytic bactericidal material.

[0038] Example 2

[0039] Using 15g of dicyandiamide (DCDA) as a precursor, the mixture was heated in a muffle furnace at 550℃ for 4.0℃ min. -1 The mixture was calcined at a high heating rate and held for 4 hours. The resulting pale yellow solid was then ground to obtain a pale yellow powder, CN (carbon nitride).

[0040] CN and NaBH4 in a mass ratio of 4:1 were finely ground in a mortar and then uniformly dispersed in a porcelain boat. The porcelain boat was then placed in a tube furnace under an argon atmosphere. The furnace program was set to heat to 400°C at a rate of 10°C / min and hold for 1 hour. After calcination, the resulting brownish-red product was washed several times with ethanol and deionized water. The washed material was then vacuum-dried at 80°C for 10 hours. The final collected brownish-red powder was designated BCN (boron-doped carbon nitride).

[0041] Application Example 1

[0042] 25 mg of the prepared carbon nitride materials HBCN, BCN, HCN, and CN were dispersed in 45 mL of 0.9% physiological saline, and 5 mL of a 1.0 × 10⁻⁶ solution was added. 8 A logCFU / mL gentamicin-resistant Escherichia coli (GEN) bacterial suspension was reacted in the dark for 20 min, followed by photocatalytic sterilization using white light as the visible light source. During the reaction, 0.1 mL of the mixture was serially diluted and plated every 60 min. The plated solid culture was then incubated at 37℃ for 24 h. The bactericidal performance of the photocatalytic material was evaluated using the plate count method. The results are as follows: Figure 2 As shown.

[0043] Application Example 2

[0044] 25 mg of the boron-oxygen dual-doped carbon nitride (HBCN) material prepared above was dispersed in 45 mL of 0.9% physiological saline, and 5 mL of 1.0 × 10⁻⁶ solution was added. 8A logCFU / mL solution of bacterial suspensions resistant to gentamicin-containing Escherichia coli (GEN), polymyxin-containing Escherichia coli (MCR), ceftazidime-containing Escherichia coli (CTX), and Staphylococcus aureus was reacted in the dark for 20 min, followed by photocatalytic sterilization using white light as the visible light source. During the reaction, 0.1 mL of the mixture was serially diluted and plated every 60 min. The resulting solid culture was incubated at 37℃ for 24 h, and the bactericidal performance of the photocatalytic material was evaluated using the plate count method. Figure 3 As shown, the boron-oxygen dual-doped carbon nitride material HBCN has a killing effect on the above-mentioned pathogens.

[0045] Application Example 3

[0046] 5, 10, 25, and 50 mg of the boron-oxygen dual-doped carbon nitride (HBCN) material prepared above were dispersed in 45 mL of 0.9% physiological saline, respectively, and 5 mL of 1.0 × 10⁻⁶ solution was added. 8 A logCFU / mL solution of gentamicin-resistant Escherichia coli (GEN) was reacted in the dark for 20 min, followed by photocatalytic sterilization using white light as the visible light source. During the reaction, 0.1 mL of the mixture was serially diluted and plated every 60 min. The plated solid culture was then incubated at 37℃ for 24 h. The bactericidal performance of the photocatalytic material was evaluated using the plate count method. Figure 4 The study investigated the inactivation effect of HBCN, a boron-oxygen dual-doped carbon nitride material with different concentrations, against gentamicin-induced Escherichia coli (E. coli).

[0047] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. An application of boron-oxygen dual-doped graphitic carbon nitride nanosheets in killing drug-resistant bacteria, characterized in that, The steps for killing drug-resistant bacteria are as follows: The original bacterial solution is mixed with physiological saline, and a photocatalyst is added to obtain a suspension; a light source is turned on to carry out a photocatalytic sterilization reaction; the drug-resistant bacteria are one or more of the following: gentamicin-resistant Escherichia coli, polymyxin-resistant Escherichia coli, ceftazidime-resistant Escherichia coli, and Staphylococcus aureus; the light source is a xenon lamp, an LED light source, or a natural sunlight source; the photocatalyst is boron-oxygen dual-doped graphitic carbon nitride nanosheets. The method for synthesizing the boron-oxygen dual-doped graphitic carbon nitride nanosheets includes the following steps: (1) The acid and the precursor were mixed and stirred, crystallized in an ice bath, and then dried to obtain a white powder; the white powder was placed in a muffle furnace and polymerized at high temperature to obtain oxygen-doped carbon nitride. (2) The oxygen-doped carbon nitride and boron-containing compounds were polymerized at high temperature in a tube furnace, and the reaction was followed by washing and drying to obtain the boron-oxygen dual-doped graphite phase carbon nitride nanosheets. The boron-containing compound is at least one of boric acid and sodium borohydride; The acid is one of concentrated nitric acid, concentrated sulfuric acid, acetic acid, and phosphoric acid; The precursor is at least one of urea, melamine, dicyandiamide, and thiourea.

2. The application according to claim 1, characterized in that, In step (1), the high-temperature polymerization is high-temperature calcination, the high-temperature polymerization temperature is 450℃-650℃, the time is 3-5h, and the heating rate is 2℃ / min-15℃ / min.

3. The application according to claim 1, characterized in that, In step (2), the mass ratio of oxygen-doped carbon nitride to boron-containing compound is (3-5):

1.

4. The application according to claim 1, characterized in that, In step (2), the high-temperature polymerization is high-temperature calcination, the high-temperature polymerization temperature is 300℃-600℃, the time is 30min-180min, and the heating rate is 2℃ / min-15℃ / min.

5. The application according to claim 1, characterized in that, The bacterial concentration in the suspension was 6.0-8.0 log. 10 The concentration of photocatalyst in the suspension is 100-2000 mg / L, with a concentration of CFU / mL.

Citation Information

Patent Citations

  • Preparation method and application of nitrogen defect / boron doped tubular carbon nitride photocatalyst

    CN113318764A

  • Nitrogen-defect-containing porous carbon nitride supported monatomic copper catalyst and preparation method and light nitrogen fixation application thereof

    CN115069290A